Amelioration of Alzheimer’s Disease by Gut-Pancreas-Liver-Brain Interaction in an App Knock-In Mouse Model - Mayumi Minamisawa; Yuma Sato; Eitarou Ishiguro; Tetsuyuki Taniai; Taiichi Sakamoto; Gota Kawai; Takashi Saito; Takaomi C. Saido (Life, 2021)
In this study, we observed disease progression, changes in the gut microbiota, and interactions among the brain, liver, pancreas, and intestine in a mouse model of Alzheimer’s disease (AD), in addition to attempting to inhibit disease progression through the dietary supplementation of L-arginine and limonoids. Wild-type mice (WC) and AD mice were fed a normal diet (AC), a diet supplemented with L-arginine and limonoids (ALA), or a diet containing only limonoids (AL) for 12–64 weeks. The normal diet-fed WC and AC mice showed a decrease in the diversity of the gut microbiota, with an increase in the Firmicutes/Bacteroidetes ratio, and bacterial translocation. Considerable bacterial translocation to the pancreas and intense inflammation of the pancreas, liver, brain, and intestinal tissues were observed in the AC mice from alterations in the gut microbiota. The ALA diet or AL diet-fed mice showed increased diversity of the bacterial flora and suppressed oxidative stress and inflammatory responses in hepatocytes and pancreatic cells, bacterial translocation, and neurodegeneration of the brain. These findings suggest that L-arginine and limonoids help in maintaining the homeostasis of the gut microbiota, pancreas, liver, brain, and gut in AD mice.